Non-covalent interactions reveal the protein chain δ conformation in a flexible single-residue model. Issue 9 (10th January 2023) - Imani, Zeynab; Mundlapati, Venkateswara Rao; Brenner, Valérie; Gloaguen, Eric; Le Barbu-Debus, Katia; Zehnacker-Rentien, Anne; Robin, Sylvie; Aitken, David J.; Mons, Michel
Abstract : The elusive δ conformation is revealed in a single amino acid residue derivative, thanks to a supportive N–H⋯S hydrogen bond provided by a designer cyclic thioether architecture. Abstract : The δ conformation is a local secondary structure in proteins that implicates a πamide N–H⋯N interaction between a backbone N atom and the NH of the following residue. Small-molecule models thereof have been limited so far to rigid proline-type compounds. We show here that in derivatives of a cyclic amino acid with a sulphur atom in the γ-position, specific side-chain/backbone N–H⋯S interactions stabilize the δ conformation sufficiently to allow it to compete with classical C5 and C7 H-bonded conformers.